Asset Inequality, Relative Efficieny of Formal Credit Markets and Choice of Organizational Form - Alper Duman (Izmir University of Economics, Department of Economics, 2009)
We model the organizational choice of a small firm given formal and informal credit market parameters. We observe a positive relationship between the size of the informal sector and the spread across countries. We take spread as relative inefficiency of the formal credit markets. Furthermore we also witness a convex positive relationship between the start-up costs and the size of the informal sector. The start-up costs are extremely important sunk costs for the micro and/or small enterprises. We argue that both the spread and the start-up costs are important parameters for the small enterprises in terms of the organizational choice. We provide a simple model to account for these main empirical regularities.
Keywords: F21; O17; 330; Organizational forms; Formal and Informal Credit Markets; Organisationsstruktur; Unternehmensfinanzierung; Kreditmarkt; Informelle Wirtschaft; Kapitalkosten; Unternehmensgründung